Collaborative National Quality and Efficacy Registry (CONQUER) for Scleroderma: outcomes from a multicenter US-based systemic sclerosis registry - Shanmugam, Victoria K. (Clin Rheumatol, 2019)
The Collaborative National Quality and Efficacy Registry (CONQUER) for Scleroderma is a multicenter US-based longitudinal study of patients with systemic sclerosis (SSc) within 5 years of first non-Raynaud’s symptom. The data collection methodology incorporates successful models from other SSc registries. The cohort is designed to provide linked bio-specimen and clinical outcomes data on a longitudinal cohort of SSc patients for validation of hypothesis-driven research and to provide a platform for studying patient-reported outcomes in scleroderma. The CONQUER registry was developed using the guidelines of the International Society for Biological Repositories, and was an iterative process between physicians with an expertise in SSc, patient stakeholders, and information technology experts. Enrollment commenced in June 2018. During the first 6 months of the CONQUER Scleroderma study, 151 SSc patients with less than 5 years of disease duration (from first non-Raynaud’s symptom) have been recruited. The mean age is 51 ± 14 years, 83% are female, and 60% of patients have diffuse disease. Survey completion rates are above 88% for all patient-reported outcome surveys. Bio-specimen collection rates are over 97%, and disease severity score completion rates are over 98%. Pulmonary function test data is available on 91% of patients, and echocardiography is available 80%. The CONQUER scleroderma study provides a unique and growing resource for studying scleroderma in a longitudinal, US-based population.